Criminal responsibility and lack of threat to the legal good in crimes of abstract exposure to danger - Filipczak, Mateusz (Acta Universitatis Lodziensis. Folia Iuridica, 2016)
This paper gives some consideration to criminal liability with regard to crimes of abstract exposure to danger. The aim of this discussion is an attempt at justifying a potential restriction on criminal responsibility for this type of crimes by application of a lack of danger to the legal good. The consideration concentrates on a relation between the lack of danger and the legal norm as well as legitimacy of criminal law, a definition of the abstract danger exposure and a legally protected subject with regard to legal interpretation rules.